Analisis Peneriman Sistem Ujian CBT Menggunakan Metode UTAUT (Unified Theory of Acceptance and Use of Technology) di Lingkungan Kampus - Arjuna Ginting; Roslina Roslina; Wanayumini Wanayumini (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Information system technology has been applied to all organizations, both organizations and non-profits, even though the development of information technology has been felt by the education sector. Slowly technology began to replace some of the work and activities carried out by humans. However, today's technology is still not perfectly applied. This study tries to get an idea of how the participants respond using computer technology in carrying out their exam process or better known as the Computer Based Test (CBT) based exam. Respondents were selected as many as 100 people who are willing to fill out the research questionnaire. To get good analysis results, this study uses a problem-solving method, namely by using the Unified Theory Acceptance and Use of Technology (UTAUT) with various constructs. As a result, the UTAUT method explains the acceptance of CBT users with the business expectation performance (PE) construct which has a significant effect on the acceptance and use of a system (BIUS). To measure the level of variation in the change in the independent variable on the dependent variable or the highest R-Square value in the UTAUT method is 73%. From these results it can be concluded that the UTAUT method is the best method used in this case study research.